Pengaruh Keberadaan Tempat Sampah Terpilah terhadap Efektivitas Pemilahan Sampah di Area Kampus - Sitti Rabbani Karimuna; Ainun Muthmainnah; Wa Ode Hafiza Rahman; Astri Ivo; Manli Desri Helden; Fahrezi Ramadhan (Lembaga Pengembangan Kinerja Dosen, 2026)
Solid waste management is still a major issue in supporting environmental sustainability in higher education institutions. Campus activities produce various types of waste that should be sorted directly from the source to support more effective waste management. This study aimed to examine the effect of the availability of separated waste bins on the effectiveness of waste sorting in the university environment. This research used a quantitative approach with a survey design involving 53 students who had knowledge of or experience in using separated waste bin facilities on campus. The data were collected online and analyzed using IBM SPSS Statistics through validity, reliability, normality, linearity, and simple linear regression tests. The results showed that the research instruments were reliable, with Cronbach’s Alpha values of 0.867 for variable X and 0.934 for variable Y. The data were normally distributed and had a linear relationship. The simple linear regression test showed that the availability of separated waste bins had a positive and significant effect on waste sorting effectiveness, with a significance value of 0.000 and a regression coefficient of 0.670. These findings indicate that the provision of accessible, clearly labeled, and adequate separated waste bins, accompanied by continuous education, can encourage better waste sorting behavior in academic environments.